Comercio electrónico y comportamiento del consumidor en el restaurante Huasai de la ciudad de Iquitos 2023 - Rios Rengifo, Carol Rubi (2025)
The objective of the research was to determine the relationship between electronic commerce and consumer behavior at the Huasai Loreto Restaurant, 2023. The research was applied, with a non-experimental and simple correlational design, and a quantitative approach was used. The sample was made up of 157 restaurants in the Loreto region. As a data collection technique, a content-validated questionnaire was applied, with a Cronbach's Alpha coefficient of 0.803. Subsequently, the data were analyzed using the statistical software SPSS version 25. It was concluded that there is a significant relationship between electronic commerce and consumer behavior at the Huasai Restaurant and the competitiveness of tourist restaurants in the Loreto region, reflected in a coefficient Spearman correlation of 0.720, suggesting a strong positive correlation, with a statistical significance level of p<0.05.